Improving the Skills of Implementing Inclusive Education at PAUD RA Khadijah Tabanan Bali - Sulistiyaningsih, Retno; Mubarok, Ali Syahidin; Dwiastuti, Ike; Hidajat, Helga Graciani; Fatmawiyati, Jati; Windraguri, Hajarotul Annisa; Hardinata, Jesicha Ramadhani Puteri; Rozi, Choirul; Prasetyo, Oky Bagas; Hasan, Akhmad Farroh (Universitas Nurul Jadid, 2025)
Being a basic level educational institution appointed as the organizer of inclusion education in Tabanan Regency, RA Khadijah seeks to provide the best service to parents of students who have children with special needs. This appointment occurs because of students with special needs received to study at RA Khadijah, supported by the desire of teachers to learn about the implementation of inclusion education, especially knowledge about handling children with special needs. This community services uses the Asset Based Community Development (ABCD) approach to maximize the resources owned by RA Khadijah. ABCD implemented using discovery, dream, design, define and destiny. Data collection using a questionaries to know the differences before and after community service established. This approach was chosen because the assets owned by RA Khadijah are complete, so it is necessary to empower appropriate so that the implementation of inclusion education can be carried out optimally. The result of this service is that RA Khadijah is able to inventory the strengths possessed for the implementation of inclusion education including the conditions and location of the school, the school environment and most importantly the teachers who conduct the initiative of self-development related to the knowledge and handling of children with needs by participating in activities such as webinars, following the groups on social media and present experts related to children with special needs. The teachers in RA Khadijah no one has an extraordinary educational background or psychology. This community service also concluded that the ownership of qualified human resources became one of the important assets in the development of services to the community, in this case the handling of children with special needs with the background of non -extraordinary non -educational educators. The limitations of this community service lie in the lack of support for teachers to be able to develop better teachers regarding inclusive education. The results of this community service aim to show the importance of maximum support from various parties to provide proper education, especially in the theme of inclusive education.